Effects of Cognitive Restructuring Technique and Self-Efficacy Training on Farming Anxiety of Farmers in Ibhiadan Emu Farming Community Edo State Nigeria - Emmanuel, Okoiye Ojaga; Ngozi, Ukah Petronilla; Anayochi, Nwoga (Advances in Social Sciences Research Journal, 2014)
Nigerian farming communities sometimes experience unpredictable and disastrous climatic weather condition(s) that make them apprehensive, agitated and uncomfortable. This climate change is one of the most serious environmental threats facing mankind worldwide. It affects agriculture in several ways, including its direct impact on food production. This development has grave implications in a number of ways on the well-being of farmers in Nigeria. In view of this context, this study investigated the effects of cognitive restructuring and self-efficacy training on farming anxiety of farmers in Ibhiadan Emu Farming Community Edo State Nigeria. The study adopted pre-test-post-test, control group experimental design with a 3x2x2 factorial matrix. Purposive sampling technique was used to select sixty farmers and the three villages that constitute Ibhiadan Emu Farming Community in Edo State. The participants were randomly assigned to treatment and control groups. Participants in the two treatment groups were exposed to eight weeks of cognitive restructuring technique and self-efficacy training. One instrument was used: Farmers anxiety scale (FAS) (α= 0.82). Four hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance. There was a significant main effect of treatment on farming anxiety scores of farmers F(2,58)=7.262, P<0.05. Also, there was significant main effect of age on farming anxiety scores of farmers exposed to treatments F(1,59)=12.075, P<0.05. However, there was no significant main effect of gender on farming anxiety scores of farmers exposed to treatment F(1,59)=4.403, P>0.05. Furthermore, there was no significant interaction effect of treatment, age and gender on farming anxiety scores of farmers F(3,57)=0.409, P>0.05). Cognitive restructuring technique and self-efficacy training were effective in reducing farming anxiety among farmers. The government should re-orientate farmers on how to interpret weather as to adopt good timing strategy for planting. Also, psychological intervention programmes should be put in place to help farmers overcome their state of maladjustment due to negative farming experience.